Experimental Inducibility of Supernumerary Phantom Limbs: A Series of Virtual Reality Experiments - Braun, Niclas; Berisha, Arbnor; Anders, David; Kannen, Kyra; Lux, Silke; Philipsen, Alexandra (Frontiers in Virtual Reality, 2020)
Supernumerary phantom limb (SPL) is a rare neuropsychiatric syndrome, under which patients perceive more limbs than they anatomically possess (e.g. two instead of only one right arm). Remarkably, the concurrent limb percepts can thereby differ in respect to their primarily-experienced modality, for instance, that one kinesthetic and one moving limb is experienced. Although SPLs are well documented after various neuropsychiatric conditions, their neurocognitive pathomechanisms still remain elusive. Therefore, an experimental paradigm by which such aberrant body misperceptions could be transiently induced and systematically investigated in healthy participants would be helpful. Inspired by the virtual hand illusion, we developed a virtual supernumerary limb illusion (SLI) version, in which two embodiable virtual hands are presented to the participant via a head-mounted display. One virtual hand is thereby presented medially and the other laterally aside the participant’s hidden real hand. Using this general setup, we examined the inducibility of a SLI in three consecutive experiments: Experiment 1 explored by which induction type (visuotactile congruency, visuothermal congruency and visuomotor congruency) SLI experiences can be induced most robustly, Experiment 2 whether SLIs can be induced by a combination of these induction types, and Experiment 3 how visuoproprioceptive congruency influences the inducibility of a SLI. Sense of ownership towards the virtual hands was systematically assessed by means of experience sampling and by an implicit electrodermal embodiment measure. Results reveal a robust effect of stronger sense of ownership towards the medially- than laterally-presented virtual hand, while only a subgroup of participants (on average, across experiments: ~25%) reported concomitant sense of ownership towards both virtual hands (i.e. a full-blown SLI experience). The highest SLI responder rate (~63%) was observed for the combined application of visuotactile and visuothermal congruency, whereas a combined application of visuothermal and visuoproprioceptive congruency induced the lowest SLI responder rate (~4%). In conclusion, our study demonstrates that although under specific experimental conditions, a majority of participants can be made to experience a SLI, under most conditions sense of ownership is only experienced towards one virtual hand. This indicates that multiple type-identical limb percepts are avoided to be co-instantiated by our brain, wherever possible.